2003
DOI: 10.4049/jimmunol.171.8.4006
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class I Gene Conversion Mutations Alter the CD8 T Cell Repertoire

Abstract: MHC class I molecules are highly polymorphic within populations. This diversity is thought to be the result of selective maintenance of new class I alleles formed by gene conversion. It has been proposed that rare alleles are maintained by their ability to confer resistance to common pathogens. Investigation has focused on differences in the presentation of foreign Ags by class I alleles, but the majority of peptides presented by class I molecules are self peptides used in shaping the naive T cell repertoire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Two mechanisms may be postulated. Recruitment of TCR repertoire is critically determined by both a competition between T cells to access the APCs (35,36) and precursor frequency (37,38). Thus, it may be suggested that the TCRs belonging to the repertoire activated by immunization in BALB/c mice (namely those carrying the 138-bp V␤18-J␤1.6, 113-bp V␤18-J␤1.6, and 113-bp V␤20-J␤2.7 rearrangements) have a high precursor frequency that prevents activation of other, low frequency T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms may be postulated. Recruitment of TCR repertoire is critically determined by both a competition between T cells to access the APCs (35,36) and precursor frequency (37,38). Thus, it may be suggested that the TCRs belonging to the repertoire activated by immunization in BALB/c mice (namely those carrying the 138-bp V␤18-J␤1.6, 113-bp V␤18-J␤1.6, and 113-bp V␤20-J␤2.7 rearrangements) have a high precursor frequency that prevents activation of other, low frequency T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The low avidity of these cells may underlie their cryptic behavior. Although low-avidity cells can escape thymus selection (10,32), their access to Ag is possibly limited by competition with T cells of higher avidity in BALB/c mice (33)(34)(35). Alternatively, it can be suggested that the cryptic CD8 + repertoire is positively selected only in BALB-neuT mice as an effect of thymic expression of rErrb2 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that class I polymorphisms cause significant changes in the T cell repertoire (16). We showed that when repertoires generated by closely related alleles respond to an Ag presented by one of the alleles, the repertoires respond differently, as indicated by their tetramer-binding preferences; however, these differences did not dictate whether a recipient could respond to TMEV.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown previously that gene conversion mutations can affect presentation of antigenic peptides (15). Recently, we have shown that gene conversion mutations also cause dramatic changes in the T cell repertoire, thereby impacting immune potential (16). T cell repertoire differences have been implicated in the altered ability of gene conversion variants to respond to viral infection (13); however because repertoire selection and Ag presentation are both mediated by class I, it is difficult to distinguish differences in these functions.…”
Section: Inability Of Bm14 Mice To Respond To Theiler's Murine Encephmentioning
confidence: 96%
See 1 more Smart Citation